Creating a 21st-century heroic myth around a living person: Example of the Croatian general Ante Gotovina - Domagoj Krpan (CES Working Papers, 2022)
One of the most important topics of Croatia accession to the EU was cooperation with International Criminal Tribunal for the former Yugoslavia (ICTY) in Den Haag. ICTY was created by the international community to prosecuted war crimes committed during the wars in the former Yugoslavia in the 1990es. In Croatia, there was an opinion that the court will prosecute only Serbia and there was a shock when the first indictments were sent for war crimes committed by Croatian forces. A personification of this process was general Ante Gotovina, who was accused among others as a member of a joint criminal enterprise but, in the end, he was found not guilty. At the same time, some parts of Croatian society and media started to build a mythical status around Ante Gotovina. This paper will analyze this type of media coverage and how it did shape opinion and consequentially created a modern myth around Gotovina.
Keywords: 330; Homeland War; Ante Gotovina; ICTY; breakup of Yugoslavia; myth